Caracterização do ritmo de atividade/repouso do Mocó (Kerodon Rupestris) em fotoperíodo artificial - Sousa, Rute Alves de (2006)
Kerodon rupestris (rock cavy, mocó) is an endemic caviidae of Brazilian northeast that inhabits rocky places in the semi arid region. The aim of this study was to characterize the activity/rest rhythm of the rock cavy under 12:12 h LD cycle and continuous light. In the first stage, seven animals were submitted to two light intensities (LD; 250:0 lux and 400:0 lux; 40 days each intensity). In the second stage four males were kept for 40 days in LD (470:<1 lux), for 18 days in LL 470 lux (LL470) and for 23 days in red dim light below 1 lux (LL<1). In the third stage three males were initially kept in LD 12:12 h (450:<1 lux) and after that in LL with gradual increase in light intensity each 21 days (<1 lux LL<1; 10 lux-LL10; 160 lux LL160; 450 lux LL450). In the fourth stage it was analyzed the motor activity of 16 animals in the first 10 days in LD. Motor activity was continuously recorded by passive infrared movement sensors connected to a computer and totaled in 5 min bins. The activity showed circadian and ultradian rhythms and activity peaks at phase transitions. The activity and the rest occurred in the light as well as in the dark phase, with activity mean greater in the light phase for most of the animals. The light intensity influenced the activity/rest rhythm in the first three stages and in the first stage the activity in 400 lux increased in four animals and decreases in two. In the second stage, the tau for 3 animals in LL470 was greater than 24 h; in LL<1 it was greater than 24 h for one and lower for two. In the third stage the tau decreased with the light intensity increase for animal 8. During the first days in the experimental room, the animals did not synchronize to the LD cycle with activity and rest occurring in both phases. The results indicate that the activity/rest rhythm of Kerodon rupestris can be affected by light intensity and that the synchronization to the LD cycle results from entrainment as well as masking probably as a consequence of the action of two or more oscillators with low coupling strength